Treatment of Songgo Langit Extract (Tridax procumbens) Against Blood Glucose Levels and Pancreatic Histopathology of Hyperglycemic Mice - Khoirunisa; Nurcahyani, Nuning; Ernawiati, Eti; Widiastuti, Endang Linirin (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2023)
Hyperglycemia is an early symptom of diabetes caused by the pancreas not being able to produce enough insulin. This condition can disrupt blood glucose metabolism, thereby damaging organs in the body such as the pancreas. Hyperglycemia can be treated using traditional plant medicines. Songgo Langit leaves (Tridax procumbens L.) are reported to have secondary metabolite compounds that have potential as antidiabetic drugs. This study aims to determine the effect of administering Songgo Langit leaf extract on blood glucose levels and changes in the histopathological structure of the pancreas in hyperglycemic mice induced by alloxan. Using Complete Random Design, mice were divided into 5 groups of 5 mice each. Group K (-) was a negative control (not treated), group K (+) was a positive control (only induced by alloxan), group P1 was induced by alloxan and extract of 0.45 mg/g BW, group P2 was induced by alloxan and extract 0.9 mg /g BW, and group P3 was induced by alloxan and extract 1.8 mg/g BW for 14 days. Glucose level data were analyzed using ANOVA and post hoc test with LSD. Pancreatic histopathological structure data were analyzed using the Kruskal-Wallis test and the Mann-Whitney post hoc test. The results showed that the treatment of ethanol extract of Songgo Langit leaf at doses P1, P2, and P3 were significantly able to reduce blood glucose levels by 61.70%, 65.11%, and 74.79% and was able to repair damage to pancreatic histopathology of mice induced by alloxan.